2015
DOI: 10.3133/cir1406
|View full text |Cite
|
Sign up to set email alerts
|

Understanding nutrients in the Chesapeake Bay watershed and implications for management and restoration: The Eastern Shore

Abstract: ), onlineFor more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, product, or firm names is for descriptive purposes only and does not imply endorsemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…Concentrations of nitrate above natural background levels are likely impacted by anthropogenic activity (Debrewer and others, 2007). Recent studies on the Delmarva Peninsula have shown that nitrate concentrations in groundwater increased about 2 mg/L as N in parts of the surficial aquifer used for domestic supply from 1988 to 2001 in response to increased nitrogen applications in previous decades (Denver and others, 2004;Ator and Denver, 2015). Headwater streams on the Delmarva Peninsula, which derive most of their flow as groundwater discharge from the surficial aquifer, also show nitrate concentrations above natural levels during base flow (Ator andDenver, 2015, Denver andothers, 2004).…”
Section: Groundwater Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…Concentrations of nitrate above natural background levels are likely impacted by anthropogenic activity (Debrewer and others, 2007). Recent studies on the Delmarva Peninsula have shown that nitrate concentrations in groundwater increased about 2 mg/L as N in parts of the surficial aquifer used for domestic supply from 1988 to 2001 in response to increased nitrogen applications in previous decades (Denver and others, 2004;Ator and Denver, 2015). Headwater streams on the Delmarva Peninsula, which derive most of their flow as groundwater discharge from the surficial aquifer, also show nitrate concentrations above natural levels during base flow (Ator andDenver, 2015, Denver andothers, 2004).…”
Section: Groundwater Chemistrymentioning
confidence: 99%
“…With the exception of phosphorus, these chemicals typically contribute to the major ions in groundwater affected by agricultural activities (Hamilton and others, 1993). In well-drained soils, phosphorus is typically bound to soils and sediments and not dissolved in water (Ator and Denver, 2015).…”
Section: Groundwater Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen that is leached into groundwater can advect into riparian zones (Williams et al 2014) and enter streams slowly during base flow (Howden et al 2011). In areas that have been used for agriculture for many years, groundwater can be contaminated with N and account for a significant portion of N flux into streams (Canter 1996, Howden et al 2011, Ator and Denver 2015. Because of the long residence time of groundwater, N from decades ago advects into streams today (Hamilton 2012) and will continue to do so for a long time, even if N application immediately ceased.…”
Section: Introductionmentioning
confidence: 99%